2009
DOI: 10.1128/mcb.01778-08
|View full text |Cite
|
Sign up to set email alerts
|

Preimplantation Mouse Embryos Depend on Inhibitory Phosphorylation of Separase To Prevent Chromosome Missegregation

Abstract: Separase is a critical protease that catalyzes the cleavage of sister chromatid cohesins to allow the separation of sister chromatids in the anaphase. Its activity must be inhibited prior to the onset of the anaphase. Two inhibitory mechanisms exist in vertebrates that block the protease activity. One mechanism is through binding and inhibition by securin, and another is phosphorylation on Ser1126 (in humans [Ser1121 in mice]). These two mechanisms are largely redundant. However, phosphorylation on Ser1121 is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
25
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 39 publications
0
25
1
Order By: Relevance
“…This persistent phosphorylation might affect enzymatic activity, protein-protein interactions, or subcellular localizations of proteins in the SEP-1 pathway. There are examples of phosphorylation playing such roles for many components of the separase pathway including cohesin, Cdc27 and separase itself (Huang et al, 2007;Huang et al, 2009;Kudo et al, 2009). Our finding that the reduced activity of pph-5 restores CG localization of SEP-1 in sep-1(ax110) embryos suggests that the subcellular localization of SEP-1 to CGs might be regulated by phosphorylation.…”
Section: Phosphatase Regulation Of the Separase Pathwaymentioning
confidence: 52%
“…This persistent phosphorylation might affect enzymatic activity, protein-protein interactions, or subcellular localizations of proteins in the SEP-1 pathway. There are examples of phosphorylation playing such roles for many components of the separase pathway including cohesin, Cdc27 and separase itself (Huang et al, 2007;Huang et al, 2009;Kudo et al, 2009). Our finding that the reduced activity of pph-5 restores CG localization of SEP-1 in sep-1(ax110) embryos suggests that the subcellular localization of SEP-1 to CGs might be regulated by phosphorylation.…”
Section: Phosphatase Regulation Of the Separase Pathwaymentioning
confidence: 52%
“…In some organisms such as yeast, the Cdk1-cyclin B1-dependent separase regulation appears to have been totally lost during evolution. However, as mouse genetics teach us, this form of anaphase control remains essential in mammals until today (19,20). …”
Section: Discussionmentioning
confidence: 99%
“…Although Cdk1-cyclin B1 seems able to always compensate for the loss of securin, securin cannot always substitute for Cdk1-cyclin B1 in separase regulation. For unknown reasons, murine early embryonic and post-migratory primordial germ cells express only little securin and fully rely on Cdk1-cyclin B1-dependent control of separase (19,20). Despite the importance of this securin-independent control of anaphase, it remains enigmatic whether Cdk1-cyclin B1, similar to securin, might exert not only a negative but simultaneously also a positive effect on separase.…”
mentioning
confidence: 99%
“…In addition, Dicer1 hypomorphism was associated with impaired corpus luteum (CL) function resulting from defects in angiogenesis (Otsuka et al 2008). Genome-wide miRNA expression has also been examined in whole ovaries from mice (Ro et al 2007, Mishima et al 2008, cattle (Hossain et al 2009, Huang et al 2009, Tripurani et al 2010 and pig . While these studies identified novel and ovarian-specific miRNA species, comparisons across different developmental stages were not performed.…”
Section: Introductionmentioning
confidence: 99%